Genomic regions repeatedly involved in divergence among plant‐specialized pea aphid biotypes. (23rd June 2014) - Nouhaud, P.; Peccoud, J.; Mahéo, F.; Mieuzet, L.; Jaquiéry, J.; Simon, J.‐C.
Abstract Understanding the genetic bases of biological diversification is a long‐standing goal in evolutionary biology. Here, we investigate whether replicated cases of adaptive divergence involve the same genomic regions in the pea aphid, Acyrthosiphon pisum, a large complex of genetically differentiated biotypes, each specialized on different species of legumes. A previous study identified genomic regions putatively involved in host‐plant adaptation and/or reproductive isolation by performing a hierarchical genome scan in three biotypes. This led to the identification of 11 FST outliers among 390 polymorphic microsatellite markers. In this study, the outlier status of these 11 loci was assessed in eight biotypes specialized on other host plants. Four of the 11 previously identified outliers showed greater genetic differentiation among these additional biotypes than expected under the null hypothesis of neutral evolution (α < 0.01). Whether these hotspots of genomic divergence result from adaptive events, intrinsic barriers or reduced recombination is discussed.